Fungicide Resistance Action Committee’s (FRAC) Classification Scheme of Fungicides According to Mode of Action - Frederick M. Fishel; Megan M. Dewdney (EDIS)
This revised guide addresses management of pesticide resistance and describes the Fungicide Resistance Action Committee’s (FRAC) classification of fungicides and bactericides registered for agricultural and non-agricultural use in Florida by their modes of action. A cross-reference of common names for active ingredients, along with corresponding examples of their trade names, is also provided. Written by F.M. Fishel and M.M. Dewdney, and published by the UF Department of Agronomy, November 2012.